Influence of integral and decaffeinated coffee brews on metabolic parameters of rats fed with hiperlipidemic diets - Gomes,Júlia Ariana de Souza (2013)
The objective of this study was to evaluate the influence of integral and decaffeinated coffee brews (Coffea arabica L and C. canephora Pierre) on the metabolic parameters of rats fed with hyperlipidemic diet. Thirty male Wistar rats (initial weight of 270 g ± 20 g) were used in the study, which were divided into six groups five each. The treatments were normal diet, hyperlipidemic diet, hyperlipidemic diet associated with integral coffee arabica or canephora brews (7.2 mL/kg/day) and hyperlipidemic diet associated to decaffeinated arabica, or canephora brews, using the same dosage. After 41 days, performance analyses were conducted.The rats were then euthanized and the carcasses were used for the analysis of dried ether extract and crude protein. Fractions of adipose tissue were processed for histological analysis. There was a reduction in weight gain and accumulation of lipids in the carcasses, lower diameter of adipocytes and a lower relative weight of the liver and kidneys of rats fed with hyperlipidemic diet associated with integral coffee brew. Integral coffee brew reduced the obesity in the rats receiving hyperlipidemic diet, but the same effect did not occur with the decaffeinated types.